Relationship of ABO and Rh blood groups with history of gastritis in the undergraduate medical and dental students: a cross-sectional study - Manandhar, Nilu; Bhattarai, Kushal (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: The various ABO and Rh blood groups with different distribution frequencies in the general population have been found to be associated with different diseases, most notably gastritis. Many studies have claimed Rh groups to be indifferent to such association. Nonetheless, ABO group is found to linked with chronic gastritis. The aim of this study was to estimate the frequencies of ABO and Rh blood groups and the gastritis amongst the first and second year undergraduate medical and dental students; and to study their relationships. Materials & Methods: In a descriptive, cross-sectional study, 247 study participants were enrolled. After procuring clearance from the institutional review committee and the informed and written consent from the study participants, data collection was done on the variables, year of study (first or second year), gender, blood groups (ABO and Rh) and history of gastritis (present or absent). Results: Blood group O was the commonest (n=99; 40.1%) followed by group B (n=77; 31.2%). Similarly, 239 (96.8%) participants were Rh-positive as compared to 8 (3.2%) Rh-negative. Interestingly, 46 (18.6%) of the participants reported positive history of gastritis. Participants with blood group O had the greatest odds (OR=1.64) of having history of gastritis compared with those with other blood groups combined. Distribution of study participants based on gender and history of gastritis in either systems of blood grouping shoed no significant difference in their proportions (p>0.05). Conclusion: In light of the above findings, further longitudinal studies can be designed to better asses the relationship.